AN ANALYSIS OF GOOD GOVERNANCE IN THE PUBLIC SERVICE SECTOR OF BATAM - Pratiwi, Diah Ayu; Sari, Meri Enita Puspita (Journal of Techno-Social, 2017)
In the era of regional autonomy, the application of good governance is an urgent matter in the attempt to achieve local good governance that is effective, efficient, and free of corruption. Public service reform is not only the main agenda of the central government, but also the main agenda of the local government. Renewal of local public services can promote the sustainability of local good governance. The purpose of this study is to find out the implementation of good governance in the public service sector in the city of Batam. This study uses the application of the principles of good governance, namely participation, accountability, transparency, responsiveness and equity in view of good governance in public service in the city of Batam. The method used was a qualitative research, specifically the case study method. Results of the study explained that the implementation of good governance in public service in the city of Batam is still not optimal. This is because some of the indicators in the principle of good governance, including the principles of participation and community participation were limited to MUSREMBANG and PNPM Mandiri. In terms of accountability in the public service, only 34% of SKPD were already implementing service standards and as much as 66% have not implemented the standard service. In terms of transparency, only one SKPD was found to be ensuring transparency. In terms of equity, it was found to be lack of public services that facilitate accessibility for users with special needs.